Determination of the potentiality of different sesame (Sesamum indicum L.) genotypes: Potentiality of different sesame (Sesamum indicum L.) genotypes (Bangladesh Journal of Agriculture, 2024)
A field experiment was carried out in Randomized Complete Block Design (RCBD) with three replications at the experimental field of Sher-e-Bangla Agricultural University (SAU) during Kharif season 2022 to know the genetic variability, correlation, and path analysis based on twelve characters of 43 sesame genotypes. Analysis of variance exhibited significant differences among the genotypes for most of the characters except the number of capsules per plant. The phenotypic variance and phenotype coefficient of variation were relatively higher than the respective genotypic variance and genotypic coefficient of variation for all the characters. High broad sense heritability together with high genetic advance in percent of mean was observed for number of secondary branches per plant (90.1%), 1000-seed weight (99.31%), and seed yield per plant (97.9%) while moderate heritability for days to 50% flowering (59.81%). The correlation coefficient analysis revealed that seed yield per plant had a significant positive correlation with plant height, days to 50% flowering, days to 80% maturity, number of primary branches per plant, number of capsules per plant, number of seeds per capsule, height of the first capsule, and 1000-seed weight. It appears from path co-efficient analysis that plant height (0.856), days to 80% maturity (0.227), number of primary branches per plant (0.467), number of secondary branches per plant (0.441), capsule length (0.258), and number of seeds per capsule (0.213) had a positive direct effect on yield per plant whereas, internode length (-0.799) followed by number of capsules per plant (-0.370), and days to 50% flowering (-0.198) had a negative direct effect. Based on mean performance, heritability and interrelationship, the genotypes G6, G12, and G36 for seed yield per plant, and the genotypes G26, G27, and G37 for early maturity could be selected for further varietal improvement of sesame.Bangladesh J. Agri. 2024, 49(1): 52-67